Radiative behavior and canopy light extinction coefficient in a savanna urban area - Andrade, Levi Pires de; Novais, Jonathan Willian Zangeski; Nogueira, Marta Cristina de Jesus Albuquerque; Sanches, Luciana; Nogueira, José de Souza; Musis, Carlo Ralph de (Ciência e Natura, 2020)
The knowledge of the radiative characteristics of an area is essential to understanding the flows of matter and energy. The value of the Light Extinction Coefficient (K) is a parameter that describes the efficiency of the interception of light in a given canopy, being required, as input, for several SWAP (Soil-Water-Atmosphere-Plant) models, which allow the characterization of the interactive properties among soil, plant and atmosphere concerning these exchanges of matter and energy. This study aimed to obtain the light extinction coefficient (K) for a savanna fragment located in the urban area of Cuiabá. The used data correspond to one measurement each month, totaling twelve measurements in 30 points during the period from October 2014 to September 2015. The measured variables were the LAI (Leaf Area Index), the photosynthetically active incident radiation (PARinc) and the transmitted radiation (PARtrans), and the calculated ones were the zenith angle (Zh) and the extinction coefficient (K). Was observed an annual variability for the light extinction coefficient between 0.49 and 0.69. There are seasonal changes that interfere with the canopy geometry and the position of the study area in relation to the solar radiation incidence, concluding that the K variability is predominantly temporal.